Review of Uvarovistia (Orthoptera: Tettigoniidae; Tettigoniinae): genetic data indicate a new cryptic species, Uvarovistia munzurensis sp.n. - Uluar, Onur; Yahyaoğlu, Özgül; Çiplak, Battal (Zootaxa, 2021)
Genus Uvarovistia ranged along the Zagros Mountain belt. We presented first genetic data from three species of the genus and a taxonomic rectification indicated by these data. Sequences of three mitochondrial and two nuclear gene segments were obtained from different populations. Phylogenetic and automatic species delimitation analyses consistently suggested three distinct phylogroups as U. zebra, U. satunini and the third a new species, U. munzurensis Uluar & Yahyaoğlu sp. n. Time estimation and population genetic analyses supported consistent results. The following conclusions were reached: (i) five species in the genus constitute two distinct species groups named as Zebra Group and Satunini Group, (ii) data suggest intra generic relationships as U. zebra + ((U. satunini + U. munzurensis) + (U. bakhtiara +U. iraka)), (iii) molecular clock estimations indicated a deep divergence time and no gene flow between U. satunini and U. munzurensis, (iv) although these two species cannot be clearly distinguished by morphology, range of U. munzurensis seems to be isolated from other by lowlands of Euphrates Valley, and (v) age of generic ancestor is around five million years a time corresponding to connection of Anatolian and Zagros plates, and genus radiated along Zagros belt after dispersal of ancestral stock here.